Penerapan Positive Routine dan Graduated Extinction untuk Menurunkan Perilaku Co-Sleeping pada Anak Usia Dini - Faradila Azka; Mita Aswanti Tjakrawiralaksana (Humanitas (Jurnal Psikologi), 2021)
Co-sleeping is an effective short-term solution for children with sleep onset difficulties. Co-sleeping, however, often correlates with a higher likelihood of night waking, shorter sleep duration, higher resistance to sleep, and lower sleep quality. Behaviour modification is the most effective intervention for co-sleeping. This study aims to apply the most commonly used behaviour modification techniques for co-sleeping, namely positive routine, and extinction. Parental education, feedback, and reinforcement were also carried in this program. The participant was a 5-year-old with co-sleeping problems. Results of the study indicate that these techniques are effective in reducing co-sleeping in early childhood. The child was successful in sleeping on her own and showed a reduction in sleep onset and night waking duration. Some factors support the implementation of the interventions: positive routines that well developed since infancy, the child that used regular physical activities, parenting style, and the child’s mastery of relaxation techniques. Keywords: behaviour modification, co-sleeping, graduated extinction, positive routine, sleep training